Analisis Pemasaran Melalui Strategi Harga, Pelayanan Dan Distribusi Untuk Meningkatkan Penjualan Pada UD Kelapa - Dewi Latifah; Istan Wighara Moelyono (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2022)
Economic growth success more quantitative in nature, namely the increase in the standard rate of income and outut the resulting production.Lately the economy in Indonesia relative develops, either in industry or the service sector.This is apparent with the growing and development of activities of economic activity that created and performed by a business entity, organization, or individual efforts to meet the needs.Along with the efforts of the fulfillment of those needs, the existence of the trade of coconut is also very helpful in the implementation of the activities of the economy.Businesses engaged in the trading, always striving to meet the needs of the community with the effort of improving pricing strategies, distribution service, and to increase sales at UD Nganjuk Coconut.UD Coconut Nganjuk should know the factors that influenced the increase in sales.UD Nganjuk Coconut will have to make some improvements and innovations that can increase sales.This research aims to menganilisis how big an influence pricing strategies, distribution services and to increase sales.Sampling method used is the Accidental Sampling Sample Method. in this study was 100 people customers in Her Palm and then UD conducted an analysis of the data obtained by using data analysis quantitative.Quantitative analysis include: test validity and reliability, test the assumptions of multiple regression analysis, classical, hypothesis testing through t-test and F-test, as well as the analysis of the coefficient of determination (R2).